TEACHING CHALLENGES IN INDONESIA: MOTIVATING STUDENTS AND TEACHERS’ CLASSROOM LANGUAGE - Yulia, Yuyun (Indonesian Journal of Applied Linguistics, 2013)
Abstract: This paper critically describes the main challenges English language teachers face in teaching in Indonesia. The subjects of the research were students and English teachers in twelve randomly selected junior high schools in government and private schools in five districts in Yogyakarta Province. A survey schedule, interviews with English language teachers, focus group discussions with students and class observation were used to gather the data. The results show that students’ motivation is more of an instrumental motivation, due to the requirements of the mandated national examination though English now is a global language and the 2006 curriculum targets communicative competence. On the other hand, the data indicated that teachers found English difficult to use in class. The classroom instruction was conducted mostly in the low variety of Bahasa Indonesia and in Javanese. The teachers claimed that it was due to students’ low motivation; in fact, the students’ eagerness to listen to the teachers as the models of English language expressions was good. Teachers need to motivate students to learn English by improving their teaching techniques as well as their speaking competence in class to achieve student integrative motivation as English is valuable for them.